Banking Services and Financial Performance of MSMEs in Indonesia’s Fashion Industry: A Resource-Based View Analysis - Reni Fitriani; Murpin Sembiring; Tommy Christian Efrata; Christian Herdinata (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study investigates the complex interrelationships between business innovation, financial management, banking services, and financial performance among fashion industry MSMEs in Indonesia. This study employed a quantitative research design with both descriptive and explanatory components. Drawing on data from a comprehensive sample across key regions, we employ structural equation modeling to examine both direct relationships and mediation effects. Our findings reveal that business innovation functions as the predominant driver of financial performance through dual mechanisms: a strong direct pathway and an indirect pathway mediated by banking services. Contrary to theoretical expectations, financial management practices primarily enhance performance through banking service utilization rather than through direct effects. Banking services emerge as a crucial mediating mechanism that translates organizational capabilities into enhanced financial outcomes. These results extend resource-based theory by illuminating specific pathways through which organizational capabilities generate competitive advantage and enhance financial intermediation theory by demonstrating that intermediation benefits are contingent on firm-level capabilities. For practitioners and policymakers, our study underscores the strategic importance of innovation development while highlighting how financial management practices can optimize external financial relationships. The research contributes to both theoretical advancement and practical understanding of capability-performance linkages in emerging economy contexts.